2020
DOI: 10.5005/jp-journals-10005-1818
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Efficacy of Cinnamon Bark Oil Incorporated and Probiotic Blend Incorporated Mucoadhesive Patch against Salivary Streptococcus mutans in Caries Active 7–10-year-old Children: An In Vivo Study

Abstract: A bstract Introduction Among the various plants studied, cinnamon has emerged as a potential herbal antimicrobial agent. Besides the medicinal plants, recently probiotics have also been recognized to affect cinnamon bark oil Streptococcus mutans (S. mutans) and other harmful oral and gut microflora. Aim and objective This placebo-controlled study aims to compare the antimicrobial potential of cinnamon bark oil incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…The studies selected were analyzed regarding the quality of the study according to the JBI criteria and the results of the analysis are presented in Table 2. Almost all aspects of the analysis were fulfilled except for 5 articles [27][28][29][30][31]. It should be noted that in one article [32] there is no real blinding, since the control group is given chewing gum and the experimental group is given yogurt, due to the different" nature" of the treatment, both subjects and researchers knew who was in the control and experimental group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies selected were analyzed regarding the quality of the study according to the JBI criteria and the results of the analysis are presented in Table 2. Almost all aspects of the analysis were fulfilled except for 5 articles [27][28][29][30][31]. It should be noted that in one article [32] there is no real blinding, since the control group is given chewing gum and the experimental group is given yogurt, due to the different" nature" of the treatment, both subjects and researchers knew who was in the control and experimental group.…”
Section: Resultsmentioning
confidence: 99%
“…Lacticaseibacillus and Bifidobacterium are the probiotic most frequently studied, and the most common species are Lacticaseibacillus rhamnosus [27,30,[33][34][35], Lacticaseibacillus paracasei [31,36,37] and Bifidobacterium longum [27,30]. Interestingly, two studies had reported the comparison of probiotics (Bifidobacterium, Lacticaseibacillus rhamnosus and Lacticaseibacillus plantarum) with the prebiotics Xylitol and Cinnamon Bark Oil [28,32].…”
Section: Resultsmentioning
confidence: 99%
“…Lacticaseibacillus and Bi dobacterium are the most frequent probiotic studied, where the most common species are Lacticaseibacillus rhamnosus (20,23,(26)(27)(28), Lacticaseibacillus paracasei (24,29,30) and Bi dobacterium longum (20,23). Interestingly, two studies had reported the comparison of probiotics (Bi dobacterium, Lacticaseibacillus rhamnosus and Lacticaseibacillus plantarum) with the prebiotics Xylitol and Cinnamon Bark Oil (21,25).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies analyze concentration of cariogenic S. mutans by culture methods. Most reported the decrease of salivary and/or plaque S. mutans counts in the probiotic group after the intervention period (21,22,(24)(25)(26)(30)(31)(32). However, only 2 studies didn´t observed statistical differences between these groups (20, 27) Some authors have compared the levels of Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, an increasing number of functional foods harboring probiotic species are developed for combating different diseases such as gastrointestinal infections, irritated bowel syndrome, constipation and dental caries (Voidarou et al., 2020; Gandhi et al., 2021; Szlufman and Shemesh, 2021). These beneficial functions of probiotic bacteria mainly rely on their inhibitory effects against the pathogens involved in these diseases.…”
Section: Discussionmentioning
confidence: 99%